The “Plan-Do-Check-Action” Plan Helps Improve the Quality of the “Standardized Training of Resident Physicians”: An Analysis of the Results of the First Pass Rate - Tang, Biyun; Lin, Danfeng; Zhang, Fengjiang; Yan, Mengling; Shao, Anwen (Frontiers in Public Health, 2021)
Background: Residency, the first several years after a college education, is a pivotal time in the development of a qualified doctor. The objective of this study was to find the problems causing the unsatisfactory performance and identify the role of the “Plan-Do-Check-Action” (PDCA) plan in providing a valuable framework for future training. Methods: STRP assessment results of 634 third-year residents from The Second Affiliated Hospital of Zhejiang University (SAHZU) were analyzed. In 2018, a total of 308 residents from 20 departments took the STRP assessment. In 2019, a total of 326 residents from 22 departments underwent the PDCA plan and took the STRP assessment. There was no change in the STRP assessment in these two years and the indicator of performance in the STRP assessment was the first pass rate (FPR). Results: A total number of 6,180 and 5,856 examinees in the Zhejiang Province took the clinical practice ability examination in 2018 and 2019, respectively. This examination was taken by 308 and 326 residents from the SAHZU in 2018 and 2019, respectively. Compared with the results in 2018, the average FPR in the Zhejiang Province increased by 2.92% from 87.87% to 90.79%. The FPR of the SAHZU increased by 7.88% from 85.06% to 92.94% . In the SAHZU, the FPRs of the Department of Emergency and Department of Anesthesiology improved 34.51% and 20.36%, respectively. There were improved results in the “Clinical Thinking and Decision-Making” and “Operation of Basic Skills” assessment stations with increases of 3.01% and 3.94%, respectively. Conclusions: Our results showed a small success of the PDCA plan in improving the quality of the STRP, especially for the residents in the Departments of Emergency and Anesthesiology. Taken together, the PDCA plan may provide a practical framework for developing future training plans.